Relationship between Self-efficacy and Health Behaviors of Faculty Members of Guilan University of Medical Science - Pour vakhshoori N. MSc; Pasha A. MSc; Ghanbari A. PhD; Atrkar Roshan Z. PhD Student (Iran University of Medical Sciences, 2011)
Background & Aim: Health behaviors have a very important role in people,s health. Self-efficacy as a person`s belief about his abilities for doing a certain behavior is an influencing factor in human behaviors. The aim of this study was to determine the relationship between self-efficacy and health behaviors in faculty members working in Guilan University of Medical Science.   Material & method: It was a descriptive correlational study. The study consisted of 203 faculty members from Guilan University of Medical Science. The data related to self - efficacy and health behaviors were collected by modified version of SRAHPS and HPLPΙΙ respectively.   Results: The research findings revealed that the faculty members have obtained %84.1 of self-efficacy and %65.9 of health behaviors scores. Chi-square Test showed a significant relationship between self-efficacy and health behaviors (P=0.0001). Pearson`s Correlation Test indicated that there was a significant relationship between self-efficacy and health behaviors and sex, age, educational level, marital status, number of children in family, monthly income and type and history of chronic illness (P=0.0001).   Conclusion: Regarding the relationship between health behaviors and self - efficacy in the study population, reinforcement of self-efficacy via education in faculty members of Guilan University of Medical Sciences is recommended.